HUBUNGAN KARIES GIGI DENGAN KUALITAS HIDUP REMAJA SMA DI KOTA JAMBI - Hendri Boy; Ahmad Khairullah (Jurnal Kesehatan Gigi, 2019)
Dental caries is tooth decay caused by plaque. Caries in adolescents is influenced by diet and oral health behaviors. Dental caries can cause physical pain and disorders of the physiological and social development of adolescents. Overall dental caries may impair the quality of life of teenagers. The purpose of this study was to determine the relationship of dental caries and quality of life for high school teenagers in the city of Jambi. The study hypothesis was no association of dental caries and the quality of life in adolescents from high school in the city of Jambi. Benefits of the research input for the Department of Dental Nursing Poltekkes Jambi MoH in the development of oral health in adolescents. The study design was analytic research with cross sectional design. The population is a high school girl in the city of Jambi Collecting data using questionnaires, examination of caries with DMF-T index, and the index measuring the quality of life by Oral Health Index Profile (OHIP). Statistical analysis by analysis chi-squre. Results of research on high school adolescents in the city of Jambi, amounting to 122 people, the majority of dental caries status in the unfavorable category which is as much as 72%. the prevalence of dental caries was 98.3%, with impaired quality of life because of dental caries in a category that is often not as much as 94.1% and there was no significant relationship (p 0.05) between caries status and quality of life of youth School in  the city of Jambi.